Socioeconomic Status and Rate of Poverty in Overweight and Obesity among Spanish Children and Adolescents - Alejandra Gallego; Jorge Olivares-Arancibia; Rodrigo Yáñez-Sepúlveda; Héctor Gutiérrez-Espinoza; José Francisco López-Gil (MDPI AG, 2024)
Background: This study aimed to analyze the relationship between socioeconomic status (SES), poverty rate, and the prevalence of overweight/obesity or obesity in children and adolescents aged 2-14. Methods: Parents or guardians reported the weight and height of participants, used to calculate body mass index (BMI) and BMI z-scores according to the International Obesity Task Force standards. Participants were categorized into "overweight/obesity" and "no overweight/obesity" and further into "obesity" and "no obesity". The rate of poverty rate was determined using data from the National Statistics Institute of Spain, defining it as the percentage of people with income below 60% of the national median. SES was based on the head of household's occupation and categorized into low, medium, and high levels. Results: Adjusted multilevel models showed participants with medium or high SES had lower odds of overweight/obesity compared to those with low SES (medium SES: odds ratio [OR]: 0.63, 95% confidence interval [CI]: 0.54-0.73; high SES: OR: 0.59, 95% CI: 0.49-0.70). Participants in the high-poverty group had higher odds of having overweight/obesity (OR: 1.40, 95% CI: 1.13-1.74) compared to the low-poverty group. Conclusions: The study highlights significant socioeconomic disparities in childhood overweight/obesity, emphasizing the potential impact of SES and poverty on health outcomes in Spanish children and adolescents.